Molecular dynamic simulation of amine-based absorption process for co2 capture - Emyra Ezzaty, Masiren (2017)
Carbon dioxide (CO2) is a major greenhouse gas that causes global warming effect. It has to be captured to reduce its concentration in the atmosphere. Amine absorption process is a promising technology to be applied for CO2 mitigation. Modeling and simulation of amine absorption process for CO2 removal at macro-scale is well established. This study was aimed to investigate the amine-CO2 absorption process at the molecular level and their intermolecular interaction during the absorption process. The study on the intermolecular interaction in amine absorption process for CO2 capture was performed using molecular dynamic (MD) simulation via Material Studio (version 7.0) software. Several case studies were conducted to investigate the effect of temperature, amine concentration, different types of alkanolamines for CO2 absorption process and comparison between single and blended amines for absorption process. Next, effect of different carbamate molecules for CO2 desorption process were also performed. The MD simulation was carried out at NVE (moles, volume, energy) 200 ps (picosecond) and NVT (moles, volume, temperature) 1 ns (nanosecond) ensemble. COMPASS and Ewald models were used within simulation box for force field and summation method calculation. Six steps were performed to simulate the selected molecules representing the CO2 absorption system which were molecular structure sketch, geometry optimisation, simulation box creation and energy minimization, simulation at equilibrium and production phase, and analysis of the last trajectory for output data for RDF (radial distribution function). RDF plot shows the relationship between r which is the distance between atom pairs in each of the trajectory distance of atom with other neighbouring atom and g(r) is the tendency of atom to interaction/probability to have interaction between atoms. The discussion of result was divided into six sections. For simulation parameter 1, the simulation results shows the strength of intermolecular interaction between MEA (monoethanolamine) solution-CO2 was increased with the increased in temperature. For simulation parameter 2, the simulation results shows the similar behavior is observed as the amount of amine concentration is increased. Due to high concentration, high basicity of MEA was produced. Hence, it tended to have strong intermolecular attraction with acidic, CO2. For simulation parameter 3, the simulation results shows the MEA solvent showed the highest tendency to interact with CO2 compared to DEA (diethanolamine) and MDEA (methyl diethanolamine) because it can directly react with CO2 and easily form carbamate ions. A good performance of activator amine, PZ (piperazine) and steric hindered amine, AMP was observed in this study. Both showed high tendency to have intermolecular interaction with water and CO2. Due to the lack of –HN bond in MDEA, this solvent was determined to be less reactive. This is because MDEA has lack of hydrogen atom attached in amino group there will be no formation of carbamate ion. MDEA cannot directly absorb CO2. Therefore, it is suggested to be blended with other reactive amines in order to increase reactivity of MDEA with CO2. For simulation parameter 4, the simulation results shows the blended MDEA/AMP and MDEA/PZ improved the efficiency of MDEA in CO2 absorption process. The addition of AMP and PZ assisted MDEA to have intermolecular interaction with CO2. For simulation parameter 5, the simulation results shows the inter- and intra-molecular interaction on stripping process showed that carbamate ions of MEA were difficult to break compared to AMP and PZ. The high tendency for inter and intra molecular interaction happened on AMP and PZ, making them a good choice to be blended with other amine solvent to overcome the limitation of other less reactive amines. The simulation results obtained from this study gave fundamental explanation on the experimental and simulations results reported in the literature. The application of MD simulation in amine absorption process is capable to improve the understanding and give insight about this process at molecular level. The research gap in this study is to investigate the influence of physical interaction between molecules on CO2 capture process by analysing system with RDF. Physical interaction between atoms or molecules will happen before chemical reaction occur. Learning about physical interaction was essential to understand the amine-based absorption process.